“El Uso de los recursos didácticos para el desarrollo de la motricidad fina de los niños y niñas del Nivel Uno de Educación Inicial de la Unidad Educativa “Dr. Alfredo Pérez Guerrero”, Cantón Guano, Provincia de Chimborazo, Año Lectivo 2015 – 2016”. - Villa Mosquera, Fernanda Janneth (2016)
The use of educational resources for the development of fine motor skills is a valuable tool for the efficient development of the capacities of children in early childhood education because it allows to successfully achieve important skills such as writing that will serve students throughout their lives. Under this provision, the research on "the use of teaching resources for the development of fine motor skills of children , Level One at “Dr. Alfredo Pérez Guerrero educational Institute” in Guano County, corresponding to Chimborazo province, during the 2015 – 2016 school year. This research arises from the need to improve the skills of teachers of level one in the use of tools for the learning of fine motor abilities. The research begins with the theoretical analysis based on previous studies and scientific foundation that supports the research. To consolidate the theoretical aspects of the theoretical foundation, an analysis of the variables was structured. A methodology was created according to the research requirements, and then an alternative guideline based on the evaluation of motor skills was carried out with the use of a Picq and P Vayer test. These includes tests of basic capabilities, and body control to determine the motor skill age of the children, as well as a laterality test. The test results allowed to determine the main shortcomings and to structure teaching resources so as to improve children’s motor skills. After performing various activities with educational resources, the same test was once again applied. Establishing through a statistical analysis that there is a significant level of improvement in the results obtained in the final test with respect to the condition in which the children were before the application of these teaching resources. So, we may conclude that the children of level one of Initial education have significantly improved his or her fine motor skills, equaling psychomotor age with chronological age, as well as ,having most children improve their laterality. Therefore, it is recommended to maintain these levels, and including in the curricular process teaching resources that must be applied with an appropriate methodology.